Antidiarrheal And Acute Toxicity Study of Ethanolic Extract of Quercus Leucotrichophora in Swiss Albino Mice - Ashok Kumar; Dr. Israr Ali (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Quercus leucotrichophora, historically used to treat various ailments, including diarrheal, was the focus of a study evaluating its antidiarrheal efficacy against castor oil-induced diarrheal in mice. The study investigated three different doses (100, 200, and 400 mg/kg) of an 80% ethanolic leaf extract of Q. leucotrichophora in Swiss albino mice, employing models of gastrointestinal transit, enteropooling, and diarrheal induced by castor oil. The results showed that, compared to the control group, the plant extract significantly reduced the frequency of both moist and total fecal output at all tested doses. The study demonstrated a significant reduction in intraluminal fluid accumulation in the group treated with the plant extract at all dose levels. Moreover, the plant extract exhibited substantial antimotility activity at higher doses when compared to the control group. In conclusion, the findings suggest that the 80% ethanolic leaf extract of Q. leucotrichophora supports the traditional claim of the plant's antidiarrheal efficacy, although further research is warranted for a more comprehensive understanding.